2021
DOI: 10.1021/acs.chemmater.1c02654
|View full text |Cite
|
Sign up to set email alerts
|

A Milestone in the Chemical Synthesis of Fe3O4 Nanoparticles: Unreported Bulklike Properties Lead to a Remarkable Magnetic Hyperthermia

Abstract: Among iron oxide phases, magnetite (Fe3O4) is often the preferred one for nanotechnological and biomedical applications because of its high saturation magnetization and low toxicity. Although there are several synthetic routes that attempt to reach magnetite nanoparticles (NPs), they are usually referred as “IONPs” (iron oxide NPs) due to the great difficulty in obtaining the monophasic and stoichiometric Fe3O4 phase. Added to this problem is the common increase of size/shape polydispersity when larger NPs (D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…These results are in good agreement with the linear response theory model, which predicts that 22 nm spherical NPs should provide the optimal mSLP response [ 22 ]. The significantly higher than expected mSLP values presented by Au@Fe-PEG NPs might be related to a higher effective anisotropy, which, as previously reported, is a crucial parameter for the magnetic HT performance of magnetic nanoparticles [ 59 , 60 ]. Further, mSLP was also tested at lower magnetic field amplitude (304 Gauss), resulting in ≈90 W/g, which is still higher than the one exhibited by other magnetic NPs at comparable magnetic field amplitude and higher frequencies [ 61 ].…”
Section: Resultsmentioning
confidence: 71%
“…These results are in good agreement with the linear response theory model, which predicts that 22 nm spherical NPs should provide the optimal mSLP response [ 22 ]. The significantly higher than expected mSLP values presented by Au@Fe-PEG NPs might be related to a higher effective anisotropy, which, as previously reported, is a crucial parameter for the magnetic HT performance of magnetic nanoparticles [ 59 , 60 ]. Further, mSLP was also tested at lower magnetic field amplitude (304 Gauss), resulting in ≈90 W/g, which is still higher than the one exhibited by other magnetic NPs at comparable magnetic field amplitude and higher frequencies [ 61 ].…”
Section: Resultsmentioning
confidence: 71%
“…The drying step contains two other seemingly innocuous variables that lead to reproducibility issues. Multiple studies have analyzed the impact of drying time and temperature on the metal–carboxylate binding mode distribution from syntheses similar to that of FeOl-1. ,,, Balakrishnan et al observed a diminishing signal from free OA with increased drying times, attributing it in part to the removal of crystal hydrate water . This change in the binding mode distribution led to a dramatic change in the resulting nanoparticles, from 6 to 13 nm for drying times from 5 to 30 days, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The two new starting materials, FeOl-2 and -3, are used in one-pot syntheses that selectively target a specific nanoparticle size without the use of an additional solvent, seed-mediated growth, or hot injection . As the OA:Fe ratio decreases, less OA is available to control the nanoparticle shape, resulting in larger, albeit nonspherical, particles (Figure f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxide superparamagnetic nanoparticles (Fe 3 O 4 MNPs) have attracted considerable scientific interest due to their superparamagnetic properties, biocompatibility, and non-toxicity, resulting in a wide range of biomedical and technological applications. For example, Fe 3 O 4 MNPs have been applied in energy storage [ 1 ]; tissue engineering [ 2 ]; protein, DNA, and cell separation from samples [ 3 , 4 ]; biosensing [ 5 ]; drug-delivery and -targeting [ 6 , 7 , 8 ]; magnetic resonance imaging (MRI) [ 9 , 10 , 11 ]; and as mediators of heat for cancer therapy (hyperthermia) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%